102k views
2 votes
Classify each conic section and write its equations in standard form. Show work.


y^2+x+10y+26=0

User JAckOdE
by
5.2k points

1 Answer

6 votes

Answer:

The conic is parabola, its equation is (y + 5)² = -(x + 1)

Explanation:

- The general equation for any conic section is

Ax² + Bxy + Cy² + Dx + Ey + F = 0

where A , B , C , D , E and F are constants. A, B, and C are not all zero

- When we change the values of some of the constants, the shape

of the corresponding conic will also change.

- It is important to know the differences in the equations to

identify the type of conic that is represented by a given equation.

# If B² − 4AC is less than zero, if a conic exists, it will be either a

circle or an ellipse

# If B² − 4AC equals zero, if a conic exists, it will be a parabola

# If B² − 4AC is greater than zero, if a conic exists, it will be a

hyperbola

* How to identify the type of the conic

- Rewrite the equation in the general form,

Ax² + Bxy + Cy² + Dx + Ey + F = 0

- Identify the values of A and C from the general form.

- If A and C are nonzero, have the same sign, and are not equal

to each other, then the graph is an ellipse.

- If A and C are equal and nonzero and have the same sign, then

the graph is a circle

- If A and C are nonzero and have opposite signs, and are not equal

then the graph is a hyperbola.

- If either A or C is zero, then the graph is a parabola

* Now lets solve the problem

- The equation is y² + x + 10y + 26 = 0

A = 0 , B = 0 , C = 1 , D = 1 , E = 10 and F = 26

∵ A = 0

∴ The equation is a parabola its standard form is:

(y - k)² = 4 p (x - h), where (h , k) is the vertex point of the parabola,

with a horizontal axis y = k

- Lets change the standard form to the general form

∵ (y - k)² = 4 p (x - h) ⇒ open the brackets

∴ y² - 2ky + k² = 4px - 4ph

- Put all of them in one side

∴ y² - 4px - 2ky + k² + 4ph = 0

- Compare it with the equation

y² - 4px - 2ky + k² + 4ph = 0 ⇒ y² + x + 10y + 26 = 0

∵ -4px = 1x ⇒ cancel x

∴ -4p = 1 ⇒ divide both sides by -4

∴ p = -1/4

∵ -2ky = 10y ⇒ cancel y

∴ -2k = 10 ⇒ divide both sides by -2

∴ k = -5

∵ k² + 4ph = 26 ⇒ (-5)² + 4(-1/4)h = 26 ⇒ simplify

∴ 25 - h = 26 ⇒ subtract 25 from both sides

∴ h = -1

- Now we can write the standard form of the equation

∴ (y - -5)² = 4(-1/4)(x - -1)

∴ (y + 5)² = -(x + 1)

User Megann
by
4.9k points